Use of comet assay for genotoxicity assessment in fishes from Gomti River - Nagpure, N S; Sharma, Shilpi; Pandey, Sanjay; Kumar, Ravindra; Srivastava, Satish K; Verma, M S; Kapoor, D (Indian Journal of Fisheries, 2011)
An increasing number of genotoxic chemicals are being released into the aquatic environment, posing serious damage to our rich aquatic biodiversity and also indirectly to human health. In view of the above, attempts have been made to explore the feasibility of application of comet assay for biomonitoring of fish from polluted sites of River Gomti in Lucknow (Uttar Pradesh), which has been exposed to heavy pollution during the recent years. For comet assay, blood samples of two fish species found in the river namely Labeo rohita and Puntius puntius , were tested. Blood samples from fishes of the same species collected from the fish ponds of the National Bureau of Fish Genetic Resources (NBFGR), Lucknow were taken as control for comparison. The samples were then subjected to comet assay for assessing DNA damage. Significant differences were observed with respect to the two important comet parameters viz. , percentage tail DNA and tail length as compared to control. The results indicated the sensitivity and suitability of comet assay for ’ in situ ’ biomonitoring programmes to explore genotoxicity of environmental pollutants.